INTEGRASI NILAI TOLERANSI DALAM PEMBELAJARAN PESANTREN: STUDI ANALISIS TERHADAP KURIKULUM DAN PRAKTIK DI PESANTREN SUNANUL HUDA, SUKABUMI - Abdillah, Abdillah; Nurlaela, Andi (LPPM STAI Al-Azhary Cianjur, 2025)
Pesantren is the oldest Islamic religious education institution in Indonesia. Pesantren has an educational curriculum that is different from the curriculum of other educational institutions. Recently, the pesantren education system has often been accused of being a source of exclusionary thinking that triggers violent acts. In particular, Western media and policy makers in the West accuse pesantren communities of being hotbeds of terrorism. This is based on the fact that acts of intolerance and violence in the name of religion will always be associated with pesantren because many perpetrators of violence and suicide bombings in various places in Indonesia involve pesantren alumni. Therefore, this study tries to analyse the thoughts of pesantren scholars and the pesantren curriculum. In this study, researchers used a qualitative approach by using the interview method and analysing the pesantren curriculum as data collection. This study concluded that the pesantren curriculum includes a moderate religious understanding. The religious understanding of the pesantren community is influenced by the education system and also the Islamic scientific lineage developed by the pesantren.